(untitled) (Indonesian Art and Justice Review, 2024)
In Indonesia, gender inequality and stereotypes are pervasive in many aspects of society, but art has emerged as a powerful tool for challenging these injustices. This paper explores the role of Indonesian art in addressing gender justice, focusing on how artists confront and deconstruct gender stereotypes through their work. By analyzing the art of prominent female and gender-nonconforming artists, as well as art produced by feminist movements, the paper highlights how art functions as a means of resistance against patriarchal norms, gender-based violence, and discrimination. The paper also discusses the impact of these artistic expressions in raising public consciousness and influencing cultural attitudes towards gender equality in Indonesia.